2015
DOI: 10.1002/chem.201406271
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Insights into Carbon Dioxide Fixation by RZnOH Species

Abstract: Organozinc hydroxides, RZnOH, possessing the proton-reactive alkylzinc group and the CO2 -reactive Zn-OH group, represent an intriguing group of organometallic precursors for the synthesis of novel zinc carbonates. Comprehensive experimental and computational investigations on 1) solution and solid-state behavior of tBuZnOH (1) species in the presence of Lewis bases, namely, THF and 4-methylpyridine; 2) step-by-step sequence of the reaction between 1 and CO2; and 3) the effect of a donor ligand and/or an exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Therefore, a thorough understanding of the mechanism of CO 2 insertion into the M-X bonds is of fundamental importance and could guide advances in the development of this important reaction. Despite the very recent large number of experimental [47][48][49][50][51][52] and theoretical [53][54][55][56][57][58][59] studies focusing on CO 2 insertion, reports on direct comparison between theoretical and experimental results remain very limited. 53,60,61 Based on the experimental findings, a plausible mechanism for CO 2 insertion into the M-X bonds (X = O or N) proposed by Nolan et al is outlined in Scheme 2.…”
Section: Development Of Catalysts Capable Of Utilising Co 2 As Feedstmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a thorough understanding of the mechanism of CO 2 insertion into the M-X bonds is of fundamental importance and could guide advances in the development of this important reaction. Despite the very recent large number of experimental [47][48][49][50][51][52] and theoretical [53][54][55][56][57][58][59] studies focusing on CO 2 insertion, reports on direct comparison between theoretical and experimental results remain very limited. 53,60,61 Based on the experimental findings, a plausible mechanism for CO 2 insertion into the M-X bonds (X = O or N) proposed by Nolan et al is outlined in Scheme 2.…”
Section: Development Of Catalysts Capable Of Utilising Co 2 As Feedstmentioning
confidence: 99%
“…Despite the very recent large number of experimental [47][48][49][50][51][52] and theoretical [53][54][55][56][57][58][59] studies focusing on CO 2 insertion, reports on direct comparison between theoretical and experimental results remain very limited. 53,60,61 To partially fill this gap, we have recently reported density functional theory based investigations of the CO 2 fixation mechanism as proposed by Nolan et al for a new Ir(I) complex, [61][62][63] [Ir(cod)I i Pr)(OH)] (1) (cod = 1,5-cyclooctadiene; I i Pr = 1,3-bis(isopropyl)imidazol-2ylidene) and its derivatives containing Ir-O (complexes 3 and 4), Ir-N (complex 5), and Ir-C bonds (complexes 6-9; see Scheme 1).…”
mentioning
confidence: 99%
“…Furthermore, some combinations of heteroleptic (L)ZnRtype complexes with homoleptic R 2 Zn compounds act as arguably the most important organozinc catalytic systems in organic synthesis 47,48 or precursors of various functional materials. 14,49 Nevertheless, the chemistry of (L)ZnR/R 2 Zn systems remains both relatively poorly understood and a subject of constant debate. 50,51 Thus, we performed controlled experiments on the reactivity of selected [(RSO 2 )ZnR]/R′ 2 Zn systems.…”
Section: Synthesis and Spectroscopic Characterisationmentioning
confidence: 99%
“…[8][9][10][11] Furthermore, it was demonstrated that reactions between selected alkylzinc hydroxides and carbon dioxide could efficiently provide novel clusters and nanomaterials based on zinc carbonates with unique physicochemical properties. [12][13][14] In turn, studies on the reactivities of homoleptic and heteroleptic organozinc compounds towards SO 2 have been explored to a lesser extent, which may seem surprising, for example, in view of the potential use of heteroleptic zinc sulfinates as catalysts for the copolymerisation of CO 2 with epoxides [15][16][17][18] or zinc bis(alkanesulfinate)s as general reagents for the formation of radical species in organic synthesis. [19][20][21][22] The latter have been usually generated from the corresponding sulfonyl chlorides by treatment with zinc dust, and the requirement of a large excess of Zn metal has restricted their employment under in situ conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, in-depth understanding of the mechanism of carbamate hydrolysis appears as a nontrivial task due to a number of possible reaction pathways including cooperative interactions of multiple molecules . In this regard, apart from the strongly basic amidine or guanidine derivatives, one of the most commonly studied CO 2 absorption systems involves polymeric species functionalized with amine moieties. , Therefore, a promising development appears to be the use of biguanide derivatives, which combine both high basicity and capabilities of internal proton transfer, but this research area appears to be surprisingly underdeveloped, with only a handful of reports related to the study of CO 2 sensing platforms based on the polyhexamethylene biguanide (PHMB) polymer. , As part of our systematic studies on both designing of various reaction systems in wet and solid state reaction environments as well as the use of CO 2 as a substrate in the preparation of functional materials, herein we confront the mechanochemical vs solution approach to CO 2 fixation by a model biguanide. Our investigations reveal that a variety of carbonate and bicarbonate products differing in molecular structures and supramolecular architectures can be formed in the studied reaction system depending on both the solvent (MeCN vs THF) and the methodology (solution vs liquid-assisted grinding (LAG)) used (Scheme ).…”
Section: Introductionmentioning
confidence: 99%